2021
DOI: 10.1186/s12909-020-02435-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a hospital-based oral health-education program on Iranian staff: evaluating a theory-driven intervention

Abstract: Background Tooth decay and periodontitis are among the most prevalent dental diseases globally with adverse effects on an individual’s general health. Recently the prevalence of dental caries has decreased significantly, but caries epidemiology remains a major problem in dental public health. This study investigated the impact of an oral health education intervention on Theory of Planned Behavior (TPB) variables, and whether changes in these variables persisted and were associated with changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(21 reference statements)
1
1
0
1
Order By: Relevance
“…It should be noted that at the end of each session, the materials were given to the participants in the form of educational pamphlets and booklets, and before each session, the contents of the previous session were briefly reviewed, which led to an increase in the construct of perceived behavioral control in the intervention group. This result was in line with the results of studies by Armoon et al (2021), Shaikh-Ahmadi et al (2019), and Ashtarian et al (2018) [ 38 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted that at the end of each session, the materials were given to the participants in the form of educational pamphlets and booklets, and before each session, the contents of the previous session were briefly reviewed, which led to an increase in the construct of perceived behavioral control in the intervention group. This result was in line with the results of studies by Armoon et al (2021), Shaikh-Ahmadi et al (2019), and Ashtarian et al (2018) [ 38 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…An OHI based on the TPB, in which the intervention group received didactic teaching and individual discussion on TPB constructs, resulted in significantly increased perceived behavioral control, flossing behavior, and reduced bleeding on probing ( 51 ). Other literature has shown that despite moderate success in using the TPB to predict intentions, an “intention-behavior gap” prevails in which the formation of intentions does not result in action ( 21 ).…”
Section: Interventions Based On Planning Behavioral Changementioning
confidence: 99%
“…Semakin keras niat seseorang untuk berperilaku maka semakin besar pula kecenderungannya untuk benar-benar mewujudkan perilaku tersebut. 29,30 Hasil uji statistik menunjukkan otonomi pribadi berhubungan dengan tindakan remaja dalam memelihara kesehatan gigi dan mulutnya.…”
Section: Pendahuluanunclassified